The challenges of getting L2 learners to use academic words in their writings - Nadarajan, Shanthi (Electronic Journal of Foreign Language Teaching, 2011)
To understand how instruction influences L2 learners to attend to academic words during writing, it is useful to look at evaluation practices, instructional approach and learner ability over time. This paper explores the relationship between academic word use and holistic scores of L2 learners’ essays, investigates L2 learners’ ability to use vocabulary following instruction, and also compares lexical richness of L1 and L2 academic writings. The multilevel data collection techniques – teacher evaluation of L1 and L2 writings, classroom interactions, excerpts from actual L1 and L2 writings and teacher reflections – provide a holistic view of L2 learners’ ability to learn words following instruction and use them like their L1 peers. Using a sample of 387 essays from 129 students, the analysis revealed that while there was no relationship between academic word use and holistic scores, not only teachers award higher grades to essays with a higher percentage of academic words, but L2 learners can also be taught to use academic vocabulary in their writings over time.